2016
DOI: 10.12659/pjr.894068
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Smoking and Myocardial Infarction Among Sudanese Male Patients Above 40 Years of Age

Abstract: SummaryTo find an association between smoking and the development of myocardial infarction in male patients above forty years of age presenting at the echocardiology department of Sudan heart center Khartoum.A prospective cohort study was carried out at the echocardiography department of Sudan Heart Center in Khartoum-Sudan between July 2012 and June 2014. The study population comprised a total of 168 adult male patients who underwent cardiac ultrasound scanning.Out of a total of 144 cases, 65% (94) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
3
7
0
2
Order By: Relevance
“…Smoking is considered an important risk factor for the development of CVD like many other chronic diseases [54]. We found an increased risk of CVD with higher DII score in smoking men.…”
Section: Discussionsupporting
confidence: 50%
“…Smoking is considered an important risk factor for the development of CVD like many other chronic diseases [54]. We found an increased risk of CVD with higher DII score in smoking men.…”
Section: Discussionsupporting
confidence: 50%
“…Acute myocardial infarction (AMI) is a severe ischemic disease responsible for cardiac fibrosis, heart failure, and sudden death [ 1 , 2 ]. It has been reported that smoking is a risk factor for the development of myocardial infarction [ 3 ]. Patients with AMI always present severe and persistent pain in the chest, which can be combined with arrhythmia, shock, or heart failure [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs), such as myocardial infarction (MI), atherosclerosis, vascular dysfunction, arrhythmias, hypertension, stroke and heart failure, lead to increased mortality in humans and the mortality rates are expected to increase to >23.6 million by 2030 ( 1 , 2 ). Interruption of the blood supply to the heart causes injury to cardiomyocytes and leads to MI ( 3 ). Diabetes mellitus (DM), or simply diabetes, is a metabolic disorder in which diabetic patients cannot appropriately regulate their blood glucose levels ( 4 ).…”
Section: Introductionmentioning
confidence: 99%